2018
DOI: 10.1186/s40594-018-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Participation and performance on paper- and computer-based low-stakes assessments

Abstract: Background: High-stakes assessments, such the Graduate Records Examination, have transitioned from paper to computer administration. Low-stakes research-based assessments (RBAs), such as the Force Concept Inventory, have only recently begun this transition to computer administration with online services. These online services can simplify administering, scoring, and interpreting assessments, thereby reducing barriers to instructors' use of RBAs. By supporting instructors' objective assessment of the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…In fall 2017, we adopted an online administration procedure that incorporates best practices for online administration based on the research literature [13]. Each term instructors complete a Qualtrics survey, which provides the start and end dates of the term and the units to be covered.…”
Section: Practical Mattersmentioning
confidence: 99%
“…In fall 2017, we adopted an online administration procedure that incorporates best practices for online administration based on the research literature [13]. Each term instructors complete a Qualtrics survey, which provides the start and end dates of the term and the units to be covered.…”
Section: Practical Mattersmentioning
confidence: 99%
“…The surveys were made available for one week, and a small amount of homework credit was awarded for survey completion. Providing a small amount of credit has been shown to help ensure that the performance of the subset of students completing an online assessment is similar to what would be obtained if the assessment were administered on paper in class [49]. All research activities for this study were deemed "exempt" by the Penn State Institutional Review Board, and those students who did not consent to have their data included in the study have been excluded from the analysis.…”
Section: B Research Instrumentsmentioning
confidence: 99%
“…Controlled use of CBA has shown to correlate positively with overall course grades in a 221‐student controlled study in General Chemistry courses at Iowa State University . On the other hand, skill inventories in a study spanning 25 sections of college physics course showed that participation in asynchronous online CBA varied significantly based on the students’ ranking within the course . Thus to increase engagement and rapid remediation for all students uniformly, the testing assessment center‐based approach developed herein promulgates an integrated testing and tutoring methodology .…”
Section: Selected Related Workmentioning
confidence: 99%